2005
DOI: 10.1002/eji.200425530
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T cell priming by B lymphocytes is CD4 help dependent

Abstract: While it is generally accepted that B lymphocytes can present antigen and activate CD4 T cells, priming of CD8 T cells by B lymphocytes remains controversial. Recently, we showed that mice injected with genetically programmed B lymphocytes generate antigen specific CD4 and CD8 T cell responses in vivo that could also be induced in mice lacking functional dendritic cells. To gain further insights into the requirements for T cell priming by antigen-presenting B lymphocytes, in vitro experiments were performed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 54 publications
4
20
0
Order By: Relevance
“…Accordingly, we found that DCprimed CTLs expressed higher levels of key cytotoxic mediators (granzyme B and IFN-γ), and upstream master regulators (T-bet, EOMES, and BLIMP-1) ( Figure 1B). Killing deficiencies observed in B cell priming were previously reported to result from impaired granzyme B expression and increased activation-induced T cell death (AICD) (41,42), which could be overcome by IL-15 and IL-21 (43,44). Consistent with earlier reports (41)(42)(43)(44), the addition of exogenous IL-15 and IL-21 during B cell priming partially rescued granzyme B expression (Supplemental Figure 1C) and AICD (Supplemental Figure 1D) in CTLs.…”
Section: Resultssupporting
confidence: 88%
“…Accordingly, we found that DCprimed CTLs expressed higher levels of key cytotoxic mediators (granzyme B and IFN-γ), and upstream master regulators (T-bet, EOMES, and BLIMP-1) ( Figure 1B). Killing deficiencies observed in B cell priming were previously reported to result from impaired granzyme B expression and increased activation-induced T cell death (AICD) (41,42), which could be overcome by IL-15 and IL-21 (43,44). Consistent with earlier reports (41)(42)(43)(44), the addition of exogenous IL-15 and IL-21 during B cell priming partially rescued granzyme B expression (Supplemental Figure 1C) and AICD (Supplemental Figure 1D) in CTLs.…”
Section: Resultssupporting
confidence: 88%
“…6), we conclude that Th-Th cooperation was key to overcome the subimmunogenicity of the -VTSA-determinant in both wild-type mice and MUC.1-Tg mice. Furthermore, the activation of CD8 T cells against the 9-mer -VTSA-peptide fits within the framework of a model in which activation of CD8 T cells by Ag-presenting B lymphocytes is Th dependent (38). Collectively, our data and interpretation of the phenomenon suggest that the immunological switch that hallmarks functionally Th-Th cooperation is the property of the APC (a B lymphocyte) where inducible costimulation plays a critical role.…”
Section: Discussionsupporting
confidence: 58%
“…There may be other cell-cell interactions that may be important during insulitis, for example the role of CD4+ cells in the activation of CD8+ cells (Castiglioni et al, 2005). Even restricting the model to the two immune cell types described in this manuscript, we could consider different clonal populations of the T cells (Khadra et al, 2011).…”
Section: Discussionmentioning
confidence: 99%